Multiplikativni učinki športa na mlade, ki se vključujejo v športne aktivnosti - Marič, Miha; Leskovar, Leskovar; Arh, Patrik; Donaval, Nejc; Tinkara Kozovinc, Tinkara Kozovinc; Kremsar, Sara; Kutnjak, Manca; Marolt, Katja; Pintarič, Katja; Ribič, Monika; Aljaž, Aljaž; Šket, Tine; et al. (2020)
Multiplicative Effects of Sport on Young People Involved in Sports Activities. Through a critical review of secondary literature sources, the involved experts prepared through mutual acquaintance, search for specific competencies of individuals and combining knowledge a synthesis of the field of sport among young people and the identification of multiplicative effects of sport on young people involved in sports activities. The cooperation was supported throughout the time by the Škofja Loka Sports Institute, which acts as a partner and on the basis of which a case study was built. During the research, through interviews and validation of experts (coaches, current and former athletes), a qualitative research was conducted on the quality of the findings and the proposed curriculums for the implementation of planned  activities. An  information  solution on the Moodle platform has also been prepared.
Keywords: management; sport; humans resource management; business process management; information systems; organization; kieziology; kineziology